The earliest gospels : the origins and transmission of the earliest Christian gospels – the contribution of the Chester Beatty Gospel Codex P⁴⁵ /: the origins and transmission of the earliest Christian gospels – the contribution of the Chester Beatty Gospel Codex P⁴⁵. (©2004) - Unknown
No abstract available